The Role of Village-Owned Enterprises (Bumdes) in Achieving Food Security and Controlling Inflation in Rejang Lebong Regency - Dennis Rydarto Tambunan; Kresnawati; Lydia Gustina Putri (CV. Era Digital Nusantara, 2025)
Villages play a role in developing food infrastructure and managing food-based community businesses through Village-Owned Enterprises (BUMDes) as a local capacity booster and driving the village economy to improve community welfare. Inflation can disrupt economic stability, reduce people's purchasing power, and create uncertainty in consumption and investment decisions. BUMDes in Rejang Lebong Regency, as coffee commodity managers, face challenges when fluctuating coffee prices impact the regional inflation rate. Strengthening aspects of production, diversification and processing, marketing and price stabilization, as well as farmer empowerment and institutional strengthening by BUMDes is expected to be able to reduce the inflation rate in the food security sector in Rejang Lebong Regency.